Impact of COVID-19 on Professions and Livelihoods of People in Kathmandu District, Nepal - Mali Malakar, Indra; Lama, Ramesh Kumar; Sapkota, Bhaba Datta (Innovative Research Journal, 2024)
The working class, referred to as the proletariat in Marxist terminology, comprises all individuals who receive compensation through wage or salary-based employment contracts. This study examined the economic impact of COVID-19 in Kathmandu district among different professions of working class, or proletariat. Using a pragmatic approach with both deductive and inductive methods, the study focused on three purposively selected municipalities in Kathmandu: Kirtipur, Kathmandu Metropolitan City, and Gokarneshwor. Respondents included private school teachers, daily wage workers, small business owners, farmers, and transportation laborers. A cluster-stratified sampling design was used, with a sample of 324 determined by Cochran’s formula. The study employed a descriptive research design, collecting both quantitative and qualitative data through interviews, focus group discussions (FGD), and key informant interviews (KII). The mean monthly income dropped from Rs.18,176.85 before the pandemic to Rs.9,518.52 during the pandemic. The lower coefficient of variation after the pandemic (31.1%) indicated a significant income effect. Financial problems were reported by 77.8% of private school teachers and a significant portion of other professions. The chi-square test (χ² = 104.864, p = 0.000) highlighted significant livelihood problems across professions. Recommendations included cash distribution (48.1%), food support in scarce areas (28.7%), and improved access to medicine (21.3%). The study draws on Keynesian theory, noting government interventions to restore employment but reveals dissatisfaction with these efforts among local victims of the pandemic. It suggests further policy development to support agricultural productivity, create emergency funds for the working class, and explore post-COVID recovery strategies.